The external focus in public and business administration a review of the literature - Gavino, Jacinto C. (Philippine Journal of Public Administration, 1986)
Both public administration and business administration exhibited parallel developments in the shift of focus from an internal to an external perspective. However, while natural differences between the two disciplines, i.e., the feedback process, the efficiency and service concept, and the scope of responsibility, raise fundamental issues as far as the role of business and government in society is concerned, the external focus of BA should be guided by the external focus of PA.